2023
DOI: 10.1002/cam4.5673
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐targeting therapy against HER3/MET in human colorectal cancers

Abstract: Background Colorectal cancer (CRC) is the most common malignancy in the world, and novel molecular targeted therapies for CRC have been vigorously pursued. We searched for novel combination therapies based on the expression patterns of membrane proteins in CRC cell lines. Results A positive correlation was observed between the expression of human pidermal growth factor receptor (HER) 3 and mesenchymal‐to‐epithelial transition factor (MET) on the cell surface of CRC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The overexpression of growth factor receptors such as EGFR, HER3, MET, and IGF1R, may be a major mechanism for the resistance of cancer cells to αHER therapies (Vu & Claret, 2012), and, thus, their combination with BsAb therapies to overcome cancer resistance is being examined (Juric et al, 2015). We showed that high affinity rather than total binding of αHER3 mAb improved combination therapies with αHER1 or αHER2 drugs (Okita et al, 2021), and suggested the efficacy of the dual targeting of HER3 and MET in the treatment of colorectal cancers (Yamasaki et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of growth factor receptors such as EGFR, HER3, MET, and IGF1R, may be a major mechanism for the resistance of cancer cells to αHER therapies (Vu & Claret, 2012), and, thus, their combination with BsAb therapies to overcome cancer resistance is being examined (Juric et al, 2015). We showed that high affinity rather than total binding of αHER3 mAb improved combination therapies with αHER1 or αHER2 drugs (Okita et al, 2021), and suggested the efficacy of the dual targeting of HER3 and MET in the treatment of colorectal cancers (Yamasaki et al, 2023).…”
Section: Introductionmentioning
confidence: 99%